2011
DOI: 10.1021/ja111021e
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Views of Molecular Conductance Perturbed by Anchor Units

Abstract: Site-specific electron transport phenomena through benzene and benzenedithiol derivatives are discussed on the basis of a qualitative Hückel molecular orbital analysis for better understanding of the effect of anchoring sulfur atoms. A recent work for the orbital control of electron transport through aromatic hydrocarbons provided an important concept for the design of high-conductance connections of a molecule with anchoring atoms. In this work the origin of the frontier orbitals of benzenedithiol derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 105 publications
5
111
0
Order By: Relevance
“…We have succeeded in applying the orbital symmetry rule to small-size aromatic hydrocarbons, 48 PAHs with different molecular sizes and edge type structures, 49 photoswitching systems, 50 and strong-coupled molecules with the electrodes. 52 According to the orbital analysis of the phase and amplitude of the HOMO and LUMO, we could easily predict possible connections and choose favorable atoms of the molecule to connect with electrodes for effective electron transport.…”
Section: Orbital Views Of Molecular Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…We have succeeded in applying the orbital symmetry rule to small-size aromatic hydrocarbons, 48 PAHs with different molecular sizes and edge type structures, 49 photoswitching systems, 50 and strong-coupled molecules with the electrodes. 52 According to the orbital analysis of the phase and amplitude of the HOMO and LUMO, we could easily predict possible connections and choose favorable atoms of the molecule to connect with electrodes for effective electron transport.…”
Section: Orbital Views Of Molecular Conductancementioning
confidence: 99%
“…48,49 Recently site-specific electron-transport phenomena are discussed on the basis of a qualitative molecular orbital analysis for better understanding of the effect of anchoring sulfur atoms. 52 MOs perturbed by the anchoring sulfur atoms still keep the electronhole symmetry, in particular combination of symmetry in the HOMO and LUMO.…”
mentioning
confidence: 99%
“…Recently, DQI has been experimentally observed in electron transport through a cross-conjugated molecular junction at room temperature [12]. Many theoretical studies on DQI involve ring-shaped conjugated molecules [4,[18][19][20][21][22][23] or cross-conjugated molecules [24] due to their simple electronic structure and the proximity of their anti-resonant states to the Fermi level of the electrodes. Moreover, ab initio calculations indicate that large conjugated molecules can enhance π-electron tunneling and suppress σ-electron tunneling [20].…”
mentioning
confidence: 99%
“…42,53 It was observed that the predicted Fermi-level conduction of a molecule with bipartite molecular graph and a non-zero HOMO-LUMO gap (specifically a Kekulean benzenoid) is large when both HOMO and LUMO have entries of large magnitude on both connection vertices (ourL andR) and the product of entries is of opposite sign for HOMO and LUMO. By the pairing theorem, this latter requirement implies that the connection vertices are in different partite sets.…”
Section: Conduction At the Fermi Levelmentioning
confidence: 99%
“…4. perturbation treatment of T(0) (for all non-ipso devices based on bipartite molecular graphs), as used in other theories of orbital contributions. 16,42,53 …”
Section: F Anthracene With An Unsymmetrical Non-ipso Devicementioning
confidence: 99%